A nanoscale natural drug delivery system for targeted drug delivery against ovarian cancer: action mechanism, application enlightenment and future potential - Li, Yi; Shen, Qian; Feng, Lu; Zhang, Chuanlong; Jiang, Xiaochen; Liu, Fudong; Pang, Bo (Frontiers in Immunology, 2024)
Ovarian cancer (OC) is one of the deadliest gynecological malignancies in the world and is the leading cause of cancer-related death in women. The complexity and difficult-to-treat nature of OC pose a huge challenge to the treatment of the disease, Therefore, it is critical to find green and sustainable drug treatment options. Natural drugs have wide sources, many targets, and high safety, and are currently recognized as ideal drugs for tumor treatment, has previously been foundto have a good effect on controlling tumor progression and reducing the burden of metastasis. However, its clinical transformation is often hindered by structural stability, bioavailability, and bioactivity. Emerging technologies for the treatment of OC, such as photodynamic therapy, immunotherapy, targeted therapy, gene therapy, molecular therapy, and nanotherapy, are developing rapidly, particularly, nanotechnology can play a bridging role between different therapies, synergistically drive the complementary role of differentiated treatment schemes, and has a wide range of clinical application prospects. In this review, nanoscale natural drug delivery systems (NNDDS) for targeted drug delivery against OC were extensively explored. We reviewed the mechanism of action of natural drugs against OC, reviewed the morphological composition and delivery potential of drug nanocarriers based on the application of nanotechnology in the treatment of OC, and discussed the limitations of current NNDDS research. After elucidating these problems, it will provide a theoretical basis for future exploration of novel NNDDS for anti-OC therapy.